2018
DOI: 10.3329/bjms.v17i4.38312
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic functions and metabolic profile of subclinical hypothyroid and hypothyroid patients.

Abstract: Objectives: Both hypercoagulable and hypocoagulable states have been proposed for hypothyroidism, whether in overt or subclinical spectrum. The status of haemostatic functions, metabolic profile and their relationship in hypothyroid disorders need to be evaluated.Methods and Material: This prospective case control study was undertaken in 30- 50 years old female subclinical and hypothyroid patients. Haemostatic functions like bleeding time (BT), clotting time (CT), prothrombin time (PT), activated partial throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a study conducted among both groups of individuals with arterial fibrillation (symptomatic and asymptomatic) when combined SCH have been revealed that increased level of TC, LDL, TG, atherogenicity and decreased level of HDL compared to control group 26 . In contrast, Mahajan et al (2018) has reported a normal homeostatic and metabolic function in both SCH and overt hypothyroid patients compared to control group 27 . However in the present study such 28 .…”
Section: Discussionmentioning
confidence: 87%
“…In a study conducted among both groups of individuals with arterial fibrillation (symptomatic and asymptomatic) when combined SCH have been revealed that increased level of TC, LDL, TG, atherogenicity and decreased level of HDL compared to control group 26 . In contrast, Mahajan et al (2018) has reported a normal homeostatic and metabolic function in both SCH and overt hypothyroid patients compared to control group 27 . However in the present study such 28 .…”
Section: Discussionmentioning
confidence: 87%
“…in patients of thalassemia major undergoing chelation therapy. 20,22,26,27,34,35 Study by Malik Zeb Khan et al (2014) shows serum ferritin used for efficient monitoring for iron chelation therapy and is suitable for ascertaining the state of iron metabolism . Study includes 50 thalassemia patients and tests done by electrochemiluminescence immune-assay technology (ECLIA) on cobase 411 Roche special immune assay analyzer.…”
Section: Ethical Clearancementioning
confidence: 99%
“…Intensive chelation therapy allows prevention and reversibility of thyroid complication.The combination of blood transfusion and chelation therapy is impor-tant in Indian context as it helps to identify the candidates of iron overloads and spare them frompsycho somatic burdens of iron overload complication which compromise their life quality and expectancy. 14,16,19,24,25,34,35 Aims & objectives: The main aim of the study was to know the effect of iron chelation in transfusion dependant thalassemia major patients with respect to serum ferritin, serum T.S.H. level before and after therapy.…”
mentioning
confidence: 99%